DFSS for shift quality using full-vehicle ADAMS model. (2nd June 2006) - Erlandson, Paul W.
Automatic transmission shift quality is a high-leverage attribute for customer satisfaction. Full-vehicle CAE models have been developed to enable prediction of shift quality before the availability of physical prototypes. The four phases of the Design for Six Sigma (DFSS) process: Define, Characterise, Optimise and Verify (DCOV) are used in conjunction with ADAMS full-vehicle models. Two candidate meta-models are developed, each of which represents a transfer function between automatic transmission torque output and a customer-correlated engineering metric, Vibration Dose Value (VDV).